2019
DOI: 10.1038/s41525-019-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted resequencing identifies genes with recurrent variation in cerebral palsy

Abstract: A growing body of evidence points to a considerable and heterogeneous genetic aetiology of cerebral palsy (CP). To identify recurrently variant CP genes, we designed a custom gene panel of 112 candidate genes. We tested 366 clinically unselected singleton cases with CP, including 271 cases not previously examined using next-generation sequencing technologies. Overall, 5.2% of the naïve cases (14/271) harboured a genetic variant of clinical significance in a known disease gene, with a further 4.8% of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…TUBA1A missense variants, for example, can have subtle effects on microtubule shape and protein interactions, which may contribute to considerable phenotype heterogeneity ( 34 ). Even in some cases where genes have been shown to have an essential role in movement in model organism studies using zebrafish or Drosophila, the human variants were not tested to confirm variant-specific effects ( 21 , 35 ).…”
Section: What Constitutes a Cp-associated Gene?mentioning
confidence: 99%
“…TUBA1A missense variants, for example, can have subtle effects on microtubule shape and protein interactions, which may contribute to considerable phenotype heterogeneity ( 34 ). Even in some cases where genes have been shown to have an essential role in movement in model organism studies using zebrafish or Drosophila, the human variants were not tested to confirm variant-specific effects ( 21 , 35 ).…”
Section: What Constitutes a Cp-associated Gene?mentioning
confidence: 99%
“…Also in 2015, the first WES study in a cohort of 201 CP cases demonstrated an important contribution of single nucleotide variants (SNVs), with a diagnostic yield of 14% (25). Another study in 2018 even reached a diagnostic yield of 65% using WES in 50 individuals with atypical CP; however, this study also included promising candidate genes whose role in CP has not been validated (26). A study in 2019, using a gene panel of 112 genes consisting of a combination of known disease genes and candidate genes classified as intolerant to variation, found genetic variants of possible clinical relevance in 10% of the CP cohort (27).…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 2018 even reached a diagnostic yield of 65% using WES in 50 individuals with atypical CP; however, this study also included promising candidate genes whose role in CP has not been validated ( 26 ). A study in 2019, using a gene panel of 112 genes consisting of a combination of known disease genes and candidate genes classified as intolerant to variation, found genetic variants of possible clinical relevance in 10% of the CP cohort ( 27 ). While the genetic causes are heterogeneous, this study identified six recurrent genes that contributed to at least 4% of disease burden in CP: COL4A1, TUBA1A, AGAP1, L1CAM, MAOB and KIF1A ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses performed in CP cohorts showed a monogenic cause in ~5% ( 27 ) to 15% ( 22 ) of cases, vastly differing between different subgroups. This factor may increase during the next years when comprehensive genetic analysis such as whole-genome sequencing (WGS) will be more broadly available and more CP genes presumably identified.…”
Section: Introductionmentioning
confidence: 99%